The Stunting Prevention Movement Through Education About Dangers of Pregnancy at an Early Age in Adolescents in SMP Negeri 2 South Tanimbar, Tanimbar Islands Regency - Saragih, Kristiova Masnita (LP2M STP Mataram, 2024)
One of the causes of stunting is teenage pregnancy where physical and psychological maturity affects the child's growth. Based on the results of the Status Monitoring survey, stunting in toddlers in the Tanimbar Islands Regency in 2022 was recorded at 31.5%. Apart from that, there was an increase in teenage pregnancies in the working area of the Saumlaki Community Health Center in the 2022 period with 20 cases, while in the January to March 2023 period there were 21 cases. In this Community Service activity, the partners are students from SMP Negeri 2 Tanimbar Selatan. There were 70 participants in this community service activity. The aim of this activity is to increase the knowledge of State Middle School students about the dangers of pregnancy at an early age as a means of preventing stunting in babies. The implementation method is through strategic activities carried out in the form of counseling or education about the dangers of pregnancy at an early age. Implementation of community service activities with the topic Stunting prevention movement through education on the impact of pregnancy at an early age on teenagers targeting students in grades VII, VIII and IX was stated to be able to provide a significant increase in knowledge for students (78.57%) about stunting compared to before it was given education (21.43%)